Graffiti writing as creative activism getting up, sheeplike subversion, and everyday resistance - Baldini, Andrea Lorenzo (2023)
Is graffiti writing creative activism? In this paper, I challenge commonly held beliefs that graffiti writing is politically inert. On the contrary, I argue that graffiti writing is an example of creative activism. Rather than being a narcissistic form of vandalism, primarily directed at increasing one’s fame in front of an esoteric group, that is, fellow writers, writing is a form of everyday resistance allowing its practitioners to challenge authoritarian power. In questioning dominant hierarchies, graffiti is a powerful tool to help correct a specific instance of spatial injustice: the unequal distribution of access to urban surfaces for self-expression in the city, where corporations and political elites hold an unjustified monopoly over visual communication.
Keywords: Aktivismus; Politische Kunst; Graffito; Engagierte Kunst